Hubungan Antara Etnik Dalam Civil Society: Analisis Perbandingan antara Studi Mansor M. Noor di Malaysia dan Asutosh Varshney di India - Khaidir, Afriva (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2005)
Even though study regarding civil society and ethnic conflict has been done for so long, but very little effort has been done to find out a relations between these two concepts. In doing so, civil society is very important as unit analysis in social science instead of in a state level as more macro analysis. Varshney and Putnam are among very little academician who pay attention to these matters. Their studies suggest the importance of civic engagement in civil society. These contacts consist of everyday engagement and associational engagement. Mansor M. Noor empirically introduces Malaysian case by composes the engagement by four level relations, they are cultural, secondary, primary and marital. The engagements make ethnic boundaries thinner and more fluid which may prevent conflict among different ethnics in society. Kata Kunci: Civil Society, konflik etnik, batas etnik